Strategi Komunikasi Dalam Bimbingan Keagamaan Islam Lansia di Rumah Pelayanan Sosial Lanjut Usia Terlantar - Azhari, Fadillah; Bahiroh, Siti (Institut Agama Islam Daruttaqwa Gresik, 2024)
This study aims to explore the communication strategies employed in Islamic religious guidance for the elderly at the Wredha Budhi Dharma Nursing Home in Umbulharjo, Yogyakarta. A qualitative descriptive approach was used, with data collected through in-depth interviews, direct observation, and documentation. The findings reveal that religious guidance is delivered in a structured manner, taking into account the physical and psychological conditions of the elderly. The communication strategies implemented by Islamic religious counselors include the use of simple language, persuasive and educational delivery techniques, and personalized approaches tailored to each individual's characteristics. Additionally, guidance activities are conducted regularly through lectures, discussions, and worship practice. The effectiveness of these communication strategies is reflected in the increased participation of the elderly in religious activities, as well as the development of inner peace and spiritual connection. This study recommends further training in communication for religious counselors to enhance the emotional and spiritual impact of the guidance provided. The implications of this study emphasize the importance of adapting communication strategies to the unique needs of the elderly, considering their physical, psychological, and spiritual conditions. It suggests that religious counselors should undergo specialized training to effectively engage with this demographic, ensuring that their guidance is not only religiously relevant but also emotionally and mentally supportive. The personalized approach to guidance, utilizing simple language, engaging techniques, and regular activities, contributes to creating a spiritually enriching environment. Additionally, the study highlights the need for religious institutions and elderly care homes to incorporate these strategies into their standard practices, potentially through the development of formal training programs for counselors and the use of modern communication tools. Furthermore, this research opens the door for future studies to explore the long-term effects of religious guidance on the emotional and spiritual well-being of the elderly, and the potential role of digital tools in making such guidance more accessible to those in institutional care settings.